NEUROTRAUMA: From Emergency Room to Back to Day-by-Day Life - Felipe Fregni (Frontiers Research Topics, 2019)
Traumatic brain injury (TBI) is a nondegenerative, noncongenital insult to the brain from an external mechanical force, possibly leading to permanent or temporary impairment of cognitive, physical, and psychosocial functions, with an associated diminished or altered state of consciousness. The definition of TBI has not been consistent and tends to vary according to specialties and circumstances. The term brain injury is often used synonymously with head injury, which may not be associated with neurological deficits. The definition has also been problematic due to variations in inclusion criteria. Both American and Brazilian data indicate that more than 700,000 people suffer TBI annually, with 20% afflicted with moderate or severe TBI. According to this data, 80% of people who suffered mild TBI can return to work, whist only 20% of moderate, and 10% of victims of severe TBI can return to their daily routine. Cognitive rehabilitation, a clinical area encompassing interdisciplinary action aimed at recovery as well as compensation of cognitive functions, altered as a result of cerebral injury, is extremely important for these individuals. The aim of a cognitive and motor rehabilitation program is to recover an individual's ability to process, interpret and respond appropriately to environmental inputs, as well as to create strategies and procedures to compensate for lost functions that are necessary in familial, social, educational and occupational relationships. In general, the cognitive rehabilitation programs tend to focus on specific cognitive domains, such as memory, motor, language and executive functions. By contrast, the focus of compensatory training procedures is generally on making environmental adaptations and changes to provide grater autonomy for patients. Successful cognitive rehabilitation programs are those whose aim is both recovery and compensation based on an integrated and interdisciplinary approach. The purpose of this Research Topic is to review the basic concepts related to TBI, including mechanisms of injury, severity levels of TBI, the most common findings in mild, moderate and severe TBI survivors, and the most cognitive and motor impairments following TBI, and also to discuss the strategies used to handle patients post-TBI. Within this context, the importance of an interdisciplinary rehabilitation for TBI is underlined.